E-Learning and Remote Education Technologies: Lessons from The Pandemic - Umar Ibrahim; JAMILU IBRAHIM ARGUNGU; Ibrahim Musa Mungadi; Ahmed Sani Yeldu (International Journal of Educational and Life Sciences, 2023)
ABSTRACT: This study explores the profound impact of e-learning and remote education technologies in the context of the COVID-19 pandemic. Through a comprehensive analysis of existing research, the article examines the advantages, challenges, and lessons learned from the sudden transition to online education. It delves into the role of digital tools, innovative strategies, and equitable access considerations in facilitating effective remote learning experiences. By discussing the implications for students, educators, and institutions, the article provides insights into the future of e-learning beyond the pandemic, emphasizing the importance of informed evolution in education.